Assessing the Priority Needs for Teacher Promotion in Private Schools in Phetchabun Province - Prasertphon, Prachya; Poohong, Chanadda; Kornpuang, Anucha; Rattanasirinichakun, Nat (The Journal of Development Administration Research, 2025)
This Article aimed to study assess the priority needs for teacher development in private schools in Phetchabun Province. The sample group consisted of 305 private school teachers in Phetchabun Province, selected using Krejcie and Morgan’s sample size table, followed by a simple random sampling method through drawing lots. The research instrument was a five-point Likert scale questionnaire designed to assess the priority needs for teacher development in private schools in the province. The statistical method used was the Priority Needs Index (PNImodified), which evaluates needs by calculating the gap between the desired state (I) and the current state (D), based on the principle of need identification through descriptive analysis of the actual conditions. The research results found that, the overall current state was rated at a moderate level. When considering individual aspects, creative thinking had the highest mean score, followed by lifelong learning. The lowest mean score was found in the curriculum aspect. As for the desired state, it was rated at a high level overall. The highest mean score was in the aspect of motivation, followed by morality, ethics, and professional code of conduct, while the lowest was in media and innovation. Regarding the Priority Needs Index (PNImodified), the overall index was 0.409. When analyzing by aspect, the curriculum had the highest priority index (0.439), followed by media and innovation (0.435), while creative thinking had the lowest index (0.376).